Aprendizagem situada e letramentos digitais no estágio supervisionado de espanhol - Elizabeth Guzzo de Almeida (2013)
This study aims at investigating the forms of participation of students in pre-service formation as Spanish teachers under the perspective of the Theory of Situated Learning. The analytical resource used has allowed us to not only understand the processes of learning enhanced by such a context but also to identify the characteristics of the local communities of practice of students and teachers of Spanish in face to face classrooms and virtual environments. To carry out the research, we conduct a case study with participant observation within an ethnographic perspective having as participants four undergraduate students in Spanish Language, two secondary teachers of Spanish and the pre-service program professor that is also the researcher of this thesis. Data have been generated through field notes, reflexive journals and in digital format such as the collaborative document Google Docs, records from portfolios and forums of the learning platform TelEduc, chat logs of online congresses, interviews taken from chats and questionnaires answered via e-mail during the study of disciplines Supervised Internship (I and II) on Spanish Teaching, in the second semester of 2010 and the first semester of 2011. Three telling cases were selected for analysis namely, the Collaborative Project, the On-line Congresses and a Workshop of back cover. In such digital literacy events, we have identified features of local communities of practice whose participants engaged themselves and formed a community, sharing language, values and behaviors in collaborative actions which called out attention due to their high level of participation. The analysis of the three telling cases as situated experiences in multiple contexts allows us to understand how the forms of participation between students and teachers involved resulted in opportunities of collaboration, feedback opportunities, and reflections. The results of this study point out that digital literacy practices are linked with participants reading and writing practices which belong to other social spaces, revealing that such process is not an autonomous phenomenon. Another relevant finding is the fact that the use of digital tools in an integrating and contextualized way to meet the teaching formation needs has strengthened the efficiency of Spanish Language learning evidenced by the attunements to constraints and affordances in the interactions promoted by the activities.